Taxonomy of the genus Plemyria Hübner (Lepidoptera, Geometridae, Larentiinae) - Choi, Sei-Woong (Entomologica Fennica, 1998)
The Holarctic genus of Plemyria comprising two species, rubiginata (Denis et Schiffermüller) and georgii (Hulst), is revised. Redescriptions of adults including the genitalia as well as larvae and pupae are given. The monophyly of the genus is discussed.